Crypto apps: How user perceptions shape continued usage? - Yohanes Ferry Cahaya; Sungkono Sungkono; Ovalia Rukmana; Jakia Rajoana; Anita Setyarachma; Johan Hendri Prasetyo; Eddy Setyanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study aims to understand and analyze how user perceptions shape sustainable usage in Crypto apps, a group of cryptocurrency exchange platforms based in Indonesia that facilitate buying, selling, and trading various digital assets. Utilizing a quantitative-causal approach, questionnaires were distributed to 245 users of several Crypto Apps in Indonesia, such as Tokocrypto, Indodax, Pintu, Rekeningku, Triv, Koinku, Upbit Indonesia, Bitocto, Zipmex, IDEX, Pluto, and Bechipin, to gather data. This study is grounded in the technology acceptance model (TAM), which postulates that perceived usefulness and ease of use significantly influence users' attitudes and behavioral intentions toward technology adoption. By applying TAM, the research seeks to identify the key factors driving sustainable usage of Crypto apps. The collected data was analyzed using SEM-PLS to examine the hypotheses. The results indicate that perceived usefulness and ease of use positively impact consumer attitudes and intention to continue using the platform. However, consumer attitude does not directly impact continuance intention and does not serve as a mediating factor. These findings hold practical implications for Crypto apps, suggesting the need to improve service quality and application features to maintain user loyalty. Moreover, the study contributes theoretically to understanding the factors influencing users’ intentions to use cryptocurrency applications. In summary, users’ perceptions of the application's benefits and ease of use significantly shape their attitudes and intentions to continue using Crypto apps.